Geographic Information System for Drought Potential Areas in Kampar District - Hanum, Nindy Raisa (Internet of Things and Artificial Intelligence Journal, 2025)
Drought is a natural disaster that has an impact on various sectors. Drought occurs during the dry season, which is from May to October. So that there is a need for spatial information in the Kampar Regency area for drought potential so that it can help overcome the problem of drought. The data consists of Landsat 8 OLI / TRIS images and rainfall data. The transformation method used is the Tasseled Cap Transformation to get the wetness and revision index and NDVI to get the vegetation index. The results of each index will be weighted and overlaid so that a map of the area with drought potential is obtained. The results of this study are Kampar District which has an area of 7% located in Tapung Hilir District, while 33% of Kampar District has a very low drought potential. In general, the Kampar Regency is classified as having moderate drought potential.